Literatura e educação no século XXI: um olhar sobre o pensamento crítico e as aulas de literatura - Boff, Amanda Ottmann (Universidade do Vale do Rio dos Sinos, 2021)
Many teenagers show a lack of interest in literature classes and reading in general, disregarding its importance in their education development. The aim of this paper is to understand the way literature classes contribute to the development of the analytical skills and their role in the educational landscape of twenty-first century. The methodology used to develop the research was a structured questionary, of open and closed questions in order to analyze the conception of literature and analytical skills of four teachers. According to the analysis, it was possible to understand that teachers who are engaged in the literary practices and in proposing literary experiences for students can involve their groups, providing more dynamic and integrative classes. Besides, this kind of classes provides an environment that is likely to provide the development of analytical skills. The conclusion is that the school of the twenty-first century is a school with literature classes since they are crucial to cause the development of the analytical skills.
Keywords: Literatura; Educação; Pensamento crítico; Literature; Education; Analytical skills